Medical students’ and teachers’ attitude: physician or patient-centered? - Moura,Noely Soares Veloso (2021)
Abstract: Introduction: Patient-centered care has been associated with positive results in medical practice. Objective: The aim of this study was to evaluate the attitudes of students and teachers from a Brazilian medical school regarding the physician-patient relationship and verify associated factors. Methods: This was an analytical cross-sectional study carried out in a public university, using the PPOS “Patient-Practitioner Orientation Scale” as well as a sociodemographic questionnaire. The subjects were regularly enrolled students attending the second semester of 2015 and their teachers. Mann-Whitney and Kruskal-Wallis tests were used to examine the effect of sociodemographic variables and the interaction with the scores found for students and teachers. Results: A total of 212 students were surveyed, corresponding to 57.1% of the enrolled students in the medical course. The value of the total PPOS score found for the students was 4.35 (± 0.5 SD), and the mean total score of PPOS among female students (4.43) was significantly higher than that in males (4.23) (p < 0.001), indicating more patient-centered attitudes in that group. Regarding medical teachers, 77 (56%) participated. The total score of PPOS was 4.52 (± 0.5 SD), with a more patient-centered attitude among teachers in comparison to students (4.35) (p = 0.001). However, there is a clear need for progress in both groups. Conclusion: The analysis of the students’ and teachers’ attitudes about the physician-patient relationship disclosed an unknown scenario, with more patient-centered attitudes verified among teachers despite the need for improvements by both. Further research is needed to evaluate not only the attitude but the behavior of these subjects.